Kebijakan Sekolah Unggul dan Akselerasi: Tinjauan Teori Sosial dan Implementasinya - Damayanti, Erika Selphie; Niswatin, Niswatin (Program Studi Pendidikan IPS Unesa, 2023)
This study aims to describe the advantages, disadvantages, and ideal characteristics of excellent schools and acceleration programs. The research adopts a qualitative descriptive method using literature review as the primary approach. The social theoretical review presents concepts and definitions regarding excellent schools and acceleration programs. Advantages of excellent schools include a quality learning environment, skilled teachers, and a curriculum focused on critical skills. Disadvantages encompass high competition and a lack of involvement in non-academic aspects. Advantages of acceleration programs are tailored academic challenges for talented and intelligent students. Disadvantages include social and emotional gaps and a limited focus on non-academic skills. The ideal depiction of excellent schools and acceleration programs involves a balanced approach to academic and non-academic needs, emotional and social support for students, and curriculum flexibility. The findings contribute valuable insights to education practitioners, policymakers, and researchers for enhancing the implementation of excellent schools and acceleration programs. In connection with curriculum renewal in the 2013 Curriculum (K13), a school policy was made with a SKS (Semester Credit Unit) system that emphasizes the ability of independent and collaborative learning of students based on the Independent Learning Activity Unit (UKBM).